Famiglia, patrimonio e strategie di transmissione della propietà in Sardegna nell’Ottocento - Monica Miscali (Nuevo mundo - Mundos Nuevos, 2008)
The Sardinian inheritance system established egalitarian propriety divisions between all heirs, females included. The propriety was transmitted from parent to children in different phases in association to the economical and productive cycles of every single family. Previously, equality was often attained during the entire life cycle of the testator, and not only through his or her single will, which could seem as non egalitarian. The rigorous egalitarian inheritance norms of the Sardinian community were acquired within the social fabric of the community, and were not only the result of laws imposed over its inhabitants. Hence, the norms reflected moral and social values more than just legal decrees which gave the heirs a certain social guarantee of fairness, when the norms were applied to individual cases. This article analyses the way the propriety inheritance system of a Sardinian community was organised in the 19th century. Some of the issues brought up here are: What were the strategies used by the rich and wealthy community owners to protect their propriety from the implications of the egalitarian inheritance mechanism? In which way did the rich and wealthy seek to keep their status after their death?